Organizational ambidexterity: a strategy for innovation and performance in start-ups (Literature review) - ETTAKANI , Doha; NAFZAOUI , MOHAMMED ACHRAF (Revue Internationale du Chercheur, 2025)
Abstract: This article explores the concept of organizational ambidexterity, which involves balancing exploitation and exploration to enhance competitiveness and innovation, particularly in startups facing limited resources and an uncertain environment, a methodological approach based on a critical literature review identifies the different types of ambidexterity (structural, contextual, and network) and their impacts, the results highlight practical strategies and managerial implications for adopting and optimizing this duality in various contexts.